Electric vehicle industry development environment evaluation in China based on BP neural network. (18th December 2014) - Xie, Chuansheng; Zhao, Chenchen; Dong, Dapeng; Zhong, Pengyuan
As an emerging industry of energy conservation and environment protection, electric vehicle industry has broad prospects for development. But now, electric car industry is in the initial stage and the development environment is complex, so it is very necessary to study the development environment. This paper combines electric vehicle industry development environment evaluation index system with BP neural network to establish the electric vehicle industry evaluation model. Then the indicator score values as training samples obtained from the use of experts scoring method are imported to the BP neural network evaluation model. After training and testing the neural network, this paper compares the testing results with the results based on analytic hierarchy process (AHP) and fuzzy comprehensive evaluation method, to test the validity of the evaluation model. The result shows that evaluation model based on BP neural network can effectively improve the reliability and accuracy of evaluation result.